Study of Physico-Chemical Parameters of the Effluent from the Wastewater Treatment Plant Hetauda and Karra River Water - Pahadi, Prakash; Adhikari, Solar; Chaubey, Srijesh (International Research Journal of MMC, 2023)
The outcome of the wastewater treatment plant (WWTP) on its usual operation was evaluated in the month of December with the help of its comparison with the running water of Karra River and with the influent from the industries located at Hetauda Industrial District (HID) area. The comparative study of water quality on the basis of their Physico-chemical parameters were carried out for final industrial waste water (S1) before entering the treatment process, waste water after the final treatment procedure (S2) and water sample from the downward stream of Karra river after the mixing of the effluent from the treatment process (S3). The sampling and other experimental processes were carried out. The parameters like temperature of the sample, turbidity, colour, odour and PH values were calculated at the respective sites while the remaining ones were carried out in the chemistry laboratory of Makawanpur multiple campus, Hetauda. The parameters like conductivity, total suspended solids, Hardness and chemical oxygen demand were calculated following standard procedures.